X-Ray Crystallographic Studied of Copper(II) Complexes with Few Drugs - Kesharwani, Rachna; Singh, Pramila (Asian Journal of Chemistry, 2010)
Few drugs, viz., diclofenac sodium, phenytoin sodium and amodiaquine hydrochloride complexes with Cu(II) have been synthesised and characterised. The present investigation reports the crystal structure studies done by X-Ray powder diffraction method. Lattice constants have been determined. The complexes of phenytoin sodium and amodiaquinehydrochloride have tetragonal while diclofenac sodium has orthorhombic geometries.